NILAI-NILAI PENDIDIKAN ISLAM DALAM PROTOKOL KESEHATAN DI MASA PANDEMI COVID-19 - Mirzon Daheri; Apri Ana Desi (Institut Agama Islam Negeri (IAIN) Tulungagung, 2021)
Abstract: The existence of counter-religious beliefs in the health protocol has resulted in resistance to its implementation. In addition, there are also issues of negative impacts on health that have exploded on various social media. So it is important to examine the perspective of religion, especially Islam, on this health protocol. This research is a research library that uses content analysis as a technique in analyzing data. Primary data to be taken is the Decree of the Minister of Health of the Republic of Indonesia number HK.01.07 / Menkes / 382/2020 regarding health protocols. The results show that the health protocol is in line with the values of Islamic education, namely the values of aqidah, morals, worship and social values.